Magical Reality of The Fantasy World - Nargiza Burieva (European Science Publishing, 2023)
The article highlights a specific type of artistic virtual reality - fantasy reality. Fantasy worlds are analyzed in the context of the development of fantastic reality. The author explored the elemental dialectic of fantasy, the relationship between fantasy "middle magic" and archaic rituals, developed a classification of fantasy heroes, revealed the spatio-temporal characteristics of fantasy reality, fantasy is shown as an actualizing reality.
Keywords: fantasy, imagination, true immortality, unknown lands, fictional, magical, reality, falsifying history.